Wogonin Inhibits Cardiac Hypertrophy by Activating Nrf-2-Mediated Antioxidant Responses. (1st July 2021) - Shi, Xiaowen; Zhang, Bin; Chu, Zhenliang; Han, Bingjiang; Zhang, Xueping; Huang, Ping; Han, Jibo
Abstract : Background . Cardiac hypertrophy is one of the initial disorders of the cardiovascular system and can induce heart failure. Oxidative stress is an important pathophysiological mechanism of cardiac hypertrophy. Wogonin (Wog), an important flavonoid derived from the root of Scutellaria baicalensis Georgi, is known to possess antioxidant properties. Methods . An in vitro model of cardiac hypertrophy was established by stimulating H9C2 cells and neonatal rat cardiomyocytes (NRCMs) with angiotensin II (AngII). The indices related to myocardial hypertrophy and oxidative stress were detected. An in vivo model of cardiac hypertrophy was induced by transverse aortic constriction (TAC) in C57BL/6 mice. Cardiac function was monitored by chest echocardiography, and the hypertrophy index was measured. The mice were then sacrificed for histological assays, with mRNA and protein detection. To further explore the role of nuclear factor- (erythroid-derived 2-) like 2 (Nrf-2) in regulating the antioxidant effects of Wog in cardiac hypertrophy, siRNA analysis was conducted. Results . Our results showed that Wog significantly ameliorated AngII-induced cardiomyocyte hypertrophy by inhibiting oxidative stress in H9C2 cells and NRCMs. In addition, Wog treatment prevented oxidative stress and improved cardiac hypertrophy in mice that underwent TAC. Using gene-specific siRNA for Nrf-2, we discovered that these antioxidative effects of Wog are mediated through Nrf-2 induction. Conclusions . Our results provide further evidence for the potential use of Wog as an antioxidative agent for treatment of cardiac hypertrophy, and Nrf-2 might serve as a therapeutic target in the treatment of cardiac hypertrophy.